Spit - Lassell, Daniel (Wheelbarrow Bks., 2021)
"The poems in Spit explore the life of a boy growing up on a farm populated with chickens, captive wolves, and a herd of llamas learning to survive among a chaotic family and coyotes. The collection in part explores the role of a body, health, and illness and humans' treatment of the earth and each other. A theme of spirituality also runs throughout the collection as the speaker treks into adulthood yearning for peace amidst the decline of his parents' marriage"--